Analisis Ekranisasi dari Novel ke Film “Little Women” - Rafa Saabira Pribadi; Askurifa'i Baksin (UNISBA Press, 2023)
Abstract. Film stories based on novels are nothing new nowadays. This adaptation process is a transfer of media, or specifically ecranisation, which can become works that can captivate audiences, both readers and viewer. This research examines the ecranisation analysis of the story “Little Women”, a novel by Louisa May Alcott (1868), which was later adapted into a film by director Greta Gerwig (2019). This study has a focus on examining the Little Women story through the theory of ecranisation in the form of shrinking plots, adding plots, or changing plot variations in the story. Data were analyzed qualitatively using the case study method through observation results with the results of interviews with related experts as additional data. The result of this study are the ecranisation aspects of the transition from the novel to the film “Little Women” dominated by changes in variation, then shrinking of the plot. There are several chapters that were adapted without any changes and some were not adapted. In reducing the plot, the director does not remove important elements from the adapted chapter. In addition, there is no element of adding grooves to the results of Little Women's ecranisation. In this film, the director uses a faithful interpretation approach, in which the director consistently maintains most of the narrative elements in following the story in the written work. The researcher also compared the narrative elements of the novel and film “Little Women” because both media have the same narrative elements. Abstrak. Film-film yang mengangkat cerita dari novel bukanlah hal yang baru pada masa kini. Proses adaptasi tersebut merupakan alih wahana, atau secara spesifik ekranisasi, yang dapat menjadi karya yang dapat memikat khalayak, baik oleh pembaca maupun penontonnya. Penelitian ini mengkaji tentang analisis ekranisasi dari cerita Little Women, sebuah novel karya Louisa May Alcott (1868), yang kemudian diadaptasi menjadi sebuah film oleh sutradara Greta Gerwig (2019). Penelitian ini memiliki fokus untuk meneliti cerita Little Women melalui teori ekranisasi berupa bentuk penciutan alur, penambahan alur, atau perubahan variasi alur pada cerita. Data dianalisis secara kualitatif dengan metode studi kasus melalui hasil observasi dengan hasil wawancara kepada ahli terkait sebagai data tambahan. Hasil temuan penelitian ini adalah aspek-aspek ekranisasi pada alih wahana dari novel ke film Little Women didominasi oleh perubahan variasi, kemudian penciutan alur. Ada beberapa bab yang diadaptasi tanpa adanya perubahan dan ada pula yang tidak diadaptasi. Selain itu, tidak ada unsur penambahan alur pada hasil ekranisasi Little Women. Pada film ini, sutradara menggunakan pendekatan interpretasi faithful, dimana sutradara konsisten menjaga sebagian besar unsur naratif dalam mengikuti cerita pada karya tulis. Peneliti juga membandingkan unsur naratif dari novel dan film Little Women karena kedua media tersebut memiliki unsur naratif yang sama.